Incorporating Cultural Elements in Language Teaching - Babaxanova Dildora Ikromjon qizi (Euro Asian Journal Publishing, 2024)
The article highlights the role of cultural elements in teaching foreign languages, emphasizing their importance for a deeper understanding of the language being studied and improving communication skills. It is emphasized that language is not only a means of communication, but also a reflection of the culture, values and worldview of the people. The article describes effective methods of incorporating cultural elements into the educational process, such as the use of authentic materials, the study of customs and traditions, as well as the use of active interaction techniques.
Keywords: teaching foreign languages; cultural elements; teaching methods